2022
DOI: 10.3389/fonc.2021.791462
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Cytokines as Early Biomarkers of Colorectal Anastomotic Leakage Following Surgery for Colorectal Cancer: A Meta-Analysis

Abstract: BackgroundPostoperative colorectal anastomotic leakage (CAL) is a devastating complication following colorectal resection. However, the diagnosis of anastomotic leakage is often delayed because the current methods of identification are unable to achieve 100% clinical sensitivity and specificity. This meta-analysis aimed to evaluate the predictive value of peritoneal fluid cytokines in the detection of CAL following colorectal surgery.MethodsA comprehensive search was conducted on PubMed, Embase, Cochrane Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…The possible reasons for this opposite result are mainly inconsistent definitions of AL and differences in inclusion criteria after careful analysis. Moreover, the updated high-quality meta-analysis 36 of eight studies further confirmed that peritoneal IL-6 levels could be used as a diagnostic marker for AL after colorectal surgery. In response to surgical stress, proinflammatory cytokines, including IL-6 and TNF-α, released from macrophages could produce an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 80%
“…The possible reasons for this opposite result are mainly inconsistent definitions of AL and differences in inclusion criteria after careful analysis. Moreover, the updated high-quality meta-analysis 36 of eight studies further confirmed that peritoneal IL-6 levels could be used as a diagnostic marker for AL after colorectal surgery. In response to surgical stress, proinflammatory cytokines, including IL-6 and TNF-α, released from macrophages could produce an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 80%
“…The limited sample size, combined with the potential risk of bias due to inconsistent criteria for defining PJI in relation to the indicators analyzed alongside IL-6, could potentially compromise the validity of the findings. In addition to conditions other than PJI, Qi et al studied postoperative patients with colorectal cancer and found that peritoneal IL-6 levels were significantly higher in the colorectal anastomotic leakage (CAL) group 1–3 days postoperatively compared to the non-CAL group (P = 0.0006, 0.0002, 0.002), suggesting that peritoneal IL-6 levels might be used as a diagnostic indicator of CAL after colorectal surgery [ 76 ]. While our umbrella review covered the majority of infectious and injurious diseases (55.9%), only Yao et al for bacterial meningitis and Shahkar et al and Qiu et al for neonatal sepsis received a "Moderate" rating in GRADE; all other meta-analyses were judged as "Low" or "Very low" in both GRADE and AMSTAR-2 [ [40] , [53] , [56] ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, when measured in blood it is a non-specific marker of systemic inflammation 19 . Peritoneal IL-6 has been measured before in AL studies and has been proposed as predictive marker for the presence of AL in patients after surgery in isolation 20 . It is broadly successful, with sensitivities and specificities in line with our measurements, but is insufficiently accurate to be used in isolation.…”
Section: Discussionmentioning
confidence: 99%